2009
DOI: 10.1002/mnfr.200800210
|View full text |Cite
|
Sign up to set email alerts
|

Naringin inhibits matrix metalloproteinase‐9 expression and AKT phosphorylation in tumor necrosis factor‐α‐induced vascular smooth muscle cells

Abstract: Citrus fruits are high in naringin, which has a beneficial effect on cardiovascular diseases. However, the matrix metalloproteinase-9 (MMP-9) regulation involved in cell migration and invasion remains to be identified. Naringin inhibited tumor necrosis factor-alpha (TNF-alpha)-induced expression of MMP-9, under 10-25 microM concentration conditions in vascular smooth muscle cells (VSMC). The TNF-alpha-induced invasion and migration of VSMC were inhibited by naringin. Furthermore, naringin suppressed TNF-alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…Arivazhagan L et al [94] reported that tangeretin treatment significantly suppressed matrix metalloproteinase (MMP)-2, MMP-9 in a DMBA-induced animal models. Lee et al [107] found that naringin extracted from Citrus fruits including grapefruit suppressed the upregulation of MMP-9 and repressed the PI3K/AKT/mTOR signaling pathway. Naringenin were evaluated for its anti-metastasis effects by Lentini et al [108].…”
Section: Anti-metastasismentioning
confidence: 99%
“…Arivazhagan L et al [94] reported that tangeretin treatment significantly suppressed matrix metalloproteinase (MMP)-2, MMP-9 in a DMBA-induced animal models. Lee et al [107] found that naringin extracted from Citrus fruits including grapefruit suppressed the upregulation of MMP-9 and repressed the PI3K/AKT/mTOR signaling pathway. Naringenin were evaluated for its anti-metastasis effects by Lentini et al [108].…”
Section: Anti-metastasismentioning
confidence: 99%
“…This finding is supported by the study of Vanamala et al and other workers in which they have reported that naringin reduced the iNOS and COX-2 expression levels by inhibiting NF-kappa B activation. 53,60) In light of the above mentioned observations, it may be reasonable to assume that the potent antioxidant and anti-inflammatory effects of naringin contributes to its anti-convulsant activity.…”
Section: )mentioning
confidence: 99%
“…Naringin has recently received considerable attention as an antioxidant dietary supplement. Recently, growing evidence has indicated that naringin or naringenin displays antiinflammatory effects both in vitro and in vivo [15][16][17][18][19]. However, there is no information regarding the effects of naringin on ALI.…”
Section: Introductionmentioning
confidence: 99%